Enhancing Steamed Bread Quality Through Co-Fermentation of Sourdough with Kazachstania humilis and Lactobacillus plantarum - Zicheng Wang; Ao Fu; Xin Wang; Guohua Zhang (Fermentation)
Sourdough fermentation, a time-honored biotechnology known for enhancing the texture, flavor, and nutritional quality of steamed bread, has yet to be fully leveraged for optimizing microbial synergy, particularly between Kazachstania humilis (KH) and Lactobacillus plantarum (LP). In this study, we systematically evaluated the impact of fermentation dynamics on sourdough properties and steamed bread quality using single-strain (KH or LP) and co-fermentation (LP+KH) strategies. Our findings demonstrated that LP+KH co-fermentation significantly accelerated sourdough acidification, achieving the lowest pH (3.8) and highest total titratable acidity (TTA, 14.2 mL) among all groups. This synergy also enhanced dough gas retention, resulting in an 11.89% and 7.25% increase in specific volume compared to LP and KH monocultures, respectively. Steamed bread produced from the co-fermented dough exhibited markedly improved textural qualities, including reduced hardness, gumminess, and chewiness, along with increased cohesiveness. Moreover, the water content in bread from the LP+KH group remained significantly higher, contributing to better freshness retention over time. In conclusion, LP and KH co-fermentation offers a promising approach for elevating the quality and shelf-life of steamed bread, revealing untapped potential in microbial synergy during sourdough fermentation.